Analysis of salivary cortisol and its relationship with burnout dimensions in prison workers - Benetti, Sabrina Azevedo Wagner; Goi, Cíntia Beatriz; Pretto, Carolina Renz; Dezordi, Cátia Matte; Benetti, Marcos; Steiernagel, Daiane Raquel; Morin, Pâmela Vione; Stumm, Eniva Miladi Fernandes (International Journal for Innovation Education and Research, 2018)
Workers in the prison system experience stress at high levels in their daily lives, so they become prone to the development of the Burnout Syndrome. In order to evaluate the occupational stress, the most sensitive and of easy access biochemical method is salivary cortisol. Aim: to evaluate the concentration of salivary cortisol in prison workers and to relate it to the Burnout Syndrome. Methodology: a cross-sectional and analytical study with 240 prison workers from the 3rd Penitentiary Region of the State of Rio Grande do Sul in Brazil, covering 8 counties and 10 prison houses. The instruments of data collection used were a sociodemographic characterization form, the Maslach Burnout Inventory and some salivary samples. The data collection period was from April to June 2017. Results: It was observed an increase in the dimensions of burnout concomitant with the increase of salivary cortisol levels in the research participants. Conclusion: The population studied experienced occupational stress evidenced by the use of the burnout and salivary cortisol instrument analysis, which is an important physiological indicator.